High-power Ge photodetector for silicon photonics has a 35 GHz bandwidth - Anon (Laser focus world, 2016)
Silicon (Si) photonic circuits are now widely used for optical interconnects and are being actively developed for many communications, instrumentation, and scientific applications. Active photonic circuit components that, like Si, are made of IV semiconductors--in particular, germanium (Ge)--are easier to integrate than are other semiconductors such as III-V semiconductors (gallium arsenide and so on). As a result, Ge photodetectors, and in particular Ge waveguide coupling detectors, are the subject of much research to improve their bandwidth and saturation power.